FATHERLESSNESS AND CHILDREN'S VULNERABILITY TO CHILD GROOMING: AN ANALYSIS FROM DEVELOPMENTAL PSYCHOLOGY AND ISLAMIC PARENTING PERSPECTIVES - Rifka Khoirun Nada; Mustolikh Khabibul Umam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of "fatherlessness" the absence of a father figure, whether physically or psychologically is an issue that impacts child development and increases vulnerability to child grooming. This study aims to analyze the relationship between fatherlessness and a child's vulnerability to becoming a victim of child grooming, while also examining the role of the father from an Islamic perspective as a preventive measure. A qualitative approach was employed using a literature review method, analyzing scholarly works, developmental psychology theories, attachment theory, and Islamic studies on parenting. The findings indicate that fatherlessness contributes to an increased risk of child grooming through five key factors: (1) the emergence of "father hunger" (a lack of paternal affection), making children susceptible to trusting others who offer attention; (2) the absence of a protective figure, which weakens supervision and the child's sense of security; (3) low self-esteem, leading children to seek validation outside the family; (4) emotional and social vulnerability resulting from a weak emotional bond with the father, making it difficult for the child to distinguish between genuine care and a perpetrator's manipulation; and (5) an increased risk of engaging in risky sexual behaviors due to a lack of supervision, communication, and the instilling of moral values ​​and boundaries. Fatherlessness also affects the child's overall social, emotional, academic, and psychological development. From an Islamic perspective, the father holds a strategic position as a leader (imam), educator, protector, and role model within the family. Efforts to prevent child grooming can be achieved through the father's active involvement in fostering open communication, providing emotional protection, monitoring the child's digital activities, educating the child on body boundaries and privacy, and remaining attentive to changes in the child's behavior. Thus, strengthening the father's role in parenting is a crucial strategy for building family resilience while minimizing the risk of children falling victim to child grooming.